Development of agricultural technologies in the Mekong Delta to respond to climate change (JIRCAS, 2016)
Contents: Rice straw, a key resource of the Mekong Delta for environmentally-friendly profitable agriculture, dissemination conditions for alternate wetting and drying irrigation in the Vietnamese Mekong Delta,...